FENOMENA PERKAWINAN DI BAWAH UMUR PERSPEKTIF AL-MASLAHAH MURSALAH - Fauzi, Ahmad Fadli Fauzi; Jumarim; Muhammad Saleh Sofyan (Al-IHKAM Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2022)
This research is motivated by the researcher's attention to the phenomenon of underage marriage in Jelantik Village, Jonggat District, Central Lombok Regency. Based on data in 2019 the number of underage marriages reached 9 people and in 2020 the number of underage marriages reached 3 people, in addition, from the marriage registration data above, currently, there are 3 underage marriage couples who have a marriage certificate and 9 couples others do not have a marriage certificate. The focus studied in this thesis is (1) what are the factors causing the phenomenon of underage marriage in Jelantik Village, Jonggat District, Central Lombok Regency? (2) what are the impacts of the phenomenon of underage marriage in Jelantik Village, Jonggat District, Central Lombok Regency? (3) how is the phenomenon of underage marriage from the perspective of al-maslahah mursalah in Jelantik Village, Jonggat District, Central Lombok Regency? This type of research uses qualitative research and uses an empirical juridical approach and a sociological approach; the data collection methods used are observation, interviews, and documentation. While the analytical method used is a qualitative analysis method. The results of this study indicate that (1) the factors causing the phenomenon of underage marriage in Jelantik Village, Jonggat District, Central Lombok Regency include: (a) low education factors; (b) cultural or environmental factors; (c) social media factors, ( d) the factor of getting pregnant out of wedlock (married by assent). (2) the impact of the phenomenon of underage marriage in Jelantik Village, Jonggat District, Central Lombok Regency, namely, positive and negative impacts. (3) the phenomenon of underage marriage from the perspective of al-maslahah mursalah in Jelantik Village, Jonggat District, Central Lombok Regency, al-maslahah mursalah can be an option in exploring and finding legal arguments such as filing a marriage dispensation for marriage registration, administratively it will provide benefits for people in marriage and can be registered legally formally by VAT. Maslahah is the goal of Islamic law; thus, where there is goodness, there is a benefit. In addition, not all underage marriages cause harm, as the researchers found in this thesis, namely, pregnant out of wedlock (MBA) and can no longer be separated so if they are not married, it will cause bigger problems. Based on this description, it can be understood that underage marriage from the perspective of al-maslahah mursalah provides a solution by way of a marriage dispensation in order to realize the benefits of underage marriage and for the sake of creating welfare for the community.